2014
DOI: 10.1073/pnas.1412062112
|View full text |Cite
|
Sign up to set email alerts
|

TSPAN12 is a critical factor for cancer–fibroblast cell contact-mediated cancer invasion

Abstract: Communication between cancer cells and their microenvironment controls cancer progression. Although the tumor suppressor p53 functions in a cell-autonomous manner, it has also recently been shown to function in a non-cell-autonomous fashion. Although functional defects have been reported in p53 in stromal cells surrounding cancer, including mutations in the p53 gene and decreased p53 expression, the role of p53 in stromal cells during cancer progression remains unclear. We herein show that the expression of α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 46 publications
(63 reference statements)
2
49
1
Order By: Relevance
“…Consistent with this, several studies reported that loss of TP53 function promotes the development of an invasive ⁄ metastatic tumor phenotype. (53,54) These observations suggest that targeting cells with aberrant TP53 function, for example, by attacking vulnerabilities cause by TP53 dysfunction (55,56) or restoring the function of abnormal TP53 protein, (57) might be an effective strategy against tumors harboring such mutations.…”
Section: Precision Ladc Medicine Based On Multistep Molecular Carcinomentioning
confidence: 99%
“…Consistent with this, several studies reported that loss of TP53 function promotes the development of an invasive ⁄ metastatic tumor phenotype. (53,54) These observations suggest that targeting cells with aberrant TP53 function, for example, by attacking vulnerabilities cause by TP53 dysfunction (55,56) or restoring the function of abnormal TP53 protein, (57) might be an effective strategy against tumors harboring such mutations.…”
Section: Precision Ladc Medicine Based On Multistep Molecular Carcinomentioning
confidence: 99%
“…TSPAN12, for example, is implicated in cancer (Knoblich et al, 2014; Otomo et al, 2014). Despite the interest in this protein family, the molecular basis of tetraspanin activity remains incompletely understood (Charrin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Luga et al revealed that CAFs-secreted exosomes promote breast cancer cell protrusive activity, motility, and metastasis via Wnt-planar cell polarity signaling[30].Some studies have demonstrated direct interactions between CAFs and cancer cells for proliferation, migration, cancer survival, and metastasis. In basal-like breast cancer and non-small cell lung cancer (NSCLC), CAFs promote proliferation, migration, and invasion of cancer cells under direct cell-to-cell contact[31][32]. Otomo et al reported that tetraspanin 12, a transmembrane protein, in CAFs facilitate NSCLC cell invasion through direct cell contact[32].…”
mentioning
confidence: 99%
“…In basal-like breast cancer and non-small cell lung cancer (NSCLC), CAFs promote proliferation, migration, and invasion of cancer cells under direct cell-to-cell contact[31][32]. Otomo et al reported that tetraspanin 12, a transmembrane protein, in CAFs facilitate NSCLC cell invasion through direct cell contact[32].…”
mentioning
confidence: 99%